2018
DOI: 10.3390/molecules23102527
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanocarriers for the Delivery of Antimalarials

Abstract: Malaria is an infectious disease caused by a protozoan parasite which is transmitted by female Anopheles mosquitoes around tropical and sub-tropical regions. Half of the world’s population is at risk of being infected by malaria. This mainly includes children, pregnant women and people living with chronic diseases. The main factor that has contributed to the spread of this disease is the increase in the number of drug-resistant parasites. To overcome drug resistance, researchers have developed drug delivery sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 70 publications
0
37
0
Order By: Relevance
“…This section includes relevant studies reported in recent years focused on polymeric nanostructures developed for drug delivery systems, polymer-based prodrugs and also prophylactic tools. 94 The last sub-section is devoted to dendrimers as a unique family of hyperbranched polymers with special features for drug conjugation.…”
Section: Polymersmentioning
confidence: 99%
“…This section includes relevant studies reported in recent years focused on polymeric nanostructures developed for drug delivery systems, polymer-based prodrugs and also prophylactic tools. 94 The last sub-section is devoted to dendrimers as a unique family of hyperbranched polymers with special features for drug conjugation.…”
Section: Polymersmentioning
confidence: 99%
“…Nanoformulations have also been investigated for malaria treatment. For this purpose, the activity of conventional antimalarial drugs has been enhanced, especially by encapsulation in liposomes, micelles, polymeric particles, cyclodextrin, and dendrimers [137][138][139][140][141][142]. The first work on the incorporation of traditional antimalarial drugs into liposomes was published in 1989 by Peeters et al [143,144].…”
Section: Formulation Techniquesmentioning
confidence: 99%
“…All the aforementioned properties make hydrogels very useful in biomedical applications such as diagnostics, regenerative medicine, tissue engineering, separation of biomolecules, cellular immobilization, drug delivery, etc. [37]. Hydrogels have been studied extensively for the treatment and management of chronic diseases such as malaria, cancer, tuberculosis, human immune virus (HIV), and influenza.…”
Section: Hydrogelsmentioning
confidence: 99%